Analisis Efektivitas Retribusi Pelayanan Persampahan/Kebersihan Pada Dinas Lingkungan Hidup Kota Tasikmalaya - Abdul Azis Ramadhan; Fransdito Ali Ilyas (POLITEKNIK LP3I, 2026)
Retribution is levied based on the services given by the local government. The correlation between retribution and services is intended as recompensation of the levy that paid by the community. This study aims analyse of the effectiveness of the waste/sanitary service retribution income and to investigate the reason why waste/sanitary service is still not optimum. This study uses qualitative methodology and the data were collected using interview technique from respondents in the Environmental Service Office, nameiy from Waste Management agency work unit they were Department Head of Waste Management, Division Head of Waste Management Service, and Division Head of Waste Facilities and Infrastructure. Besides interviews, this study also analyzes the document regarding retribution income in the Environmental Service Office. The result of this study shows that the effectiveness level of the retribution income as a whole is ineffective. It is also found that the reason for the retribution income effectiveness reduction was due to levy absorption and human resource factors. There were four factors that caused non optimum sanitary service. These factors were facilities and infrastructure, community, budget and operational.